Paternally Acting Canonical RNA-Directed DNA Methylation Pathway Genes Sensitize Arabidopsis Endosperm to Paternal Genome Dosage - Satyaki, Prasad R.V. (Plant Cell, 2019)
Seed development is sensitive to parental dosage, with excess maternal or paternal genomes creating reciprocal phenotypes. Paternal genomic excess frequently results in extensive endosperm proliferation without cellularization and seed abortion. We previously showed that loss of the RNA polymerase IV gene NUCLEAR RNA POLYMERASE D1 (NRPD1) in tetraploid fathers represses seed abortion in paternal excess crosses. Here, we show genetically that RNA-directed DNA methylation (RdDM) pathway activity in the paternal parent is sufficient to determine the viability of paternal excess Arabidopsis (Arabidopsis thaliana) seeds. We compared transcriptomes, DNA methylation, and small RNAs from the endosperm of seeds from balanced crosses (diploid × diploid) and lethal (diploid × tetraploid) and viable paternal excess crosses (diploid × tetraploid nrpd1). Endosperms from both lethal and viable paternal excess seeds share widespread transcriptional and DNA methylation changes at genes and transposable elements. Interploidy seed abortion is thus unlikely to be caused by transposable elements or imprinted gene misregulation, and its repression by the loss of paternal RdDM is associated with only modest gene expression changes. Finally, using allele-specific transcription data, we present evidence for a transcriptional buffering system that increases the expression of maternal alleles and represses paternal alleles in response to excess paternal genomic dosage. These findings prompt reconsideration of models for dosage sensitivity in endosperm.